Implications of helplessness in depression: diagnosing mild cognitive impairment and analyzing its effects on cognitive decline in older adults - Lee, Boung Chul; Choe, Young Min; Suh, Guk-Hee; Keum, Musung; Kim, Shin Gyeom; Kim, Hyun Soo; Hwang, Jaeuk; Yi, Dahyun; Kim, Jee Wook (Frontiers in Aging Neuroscience, 2024)
Background This study focuses on how elements of depression correlate with mild cognitive impairment (MCI) in older adults and the diagnostic efficacy of combining these components with the Mini-Mental State Examination (MMSE). The study also investigated the connection between individual depression components and overall cognitive function, as measured by the total score (TS) of the consortium to establish a registry for Alzheimer’s disease (AD) assessment battery. Methods The study included 196 nondemented adults aged 65 to 90 years at a university hospital and community. Comprehensive clinical assessments including the 30-item Geriatric Depression Scale (GDS) to measure components of depressive symptoms, TS, and blood nutritional biomarkers. Results Our stepwise logistic regression analysis highlighted the ‘helplessness item’ (odds ratio = 4.531, 95% CI = 2.218 to 9.258, p < 0.001) as a significant predictor for MCI diagnosis. Further, models incorporating ‘helplessness item + MMSE’ demonstrated markedly enhanced accuracy in diagnosing MCI, surpassing the performance of the MMSE used independently. Notably, the group characterized by helplessness showed a significant reduction in TS (B = −5.300, SE = 1.899, β = −0.162, p = 0.006), with this trend being particularly pronounced in individuals exhibiting lower levels of physical activity. Interestingly, this correlation did not manifest in participants with higher physical activity levels. Conclusion Our findings suggest that helplessness is highly effective in diagnosing MCI and is linked to a decrease in cognitive function. Therefore, when addressing MCI and AD-related cognitive decline, clinicians should consider helplessness.